Dialectics of knowing in education : transforming conventional practice into its opposite - Hooley, Neil (Routledge, 2018)
"Dialectics of Knowing strengthens the philosophical basis of formal education that has been weakened by neoliberalism over the past thirty years. It draws upon Greek philosophy that asked 'How should we live?' and European Enlightenment that considered 'What can we know?' to question today 'What does it mean to experience mind, to act, think and create ethically?' Focusing particularly on the notion of praxis and specific issues involving indigenous, feminist and practitioner knowing, this book will help scholars and practitioners to transform their education theories and practices in ways that encourage democracy, emancipation, social action, culture, inquiry and creativity" --